Polarization transfer in the inner-shell photoionization of sodiumlike ions - Sharma, Lalita; Surzhykov, Andrey; Inal, M. K.; Fritzsche, S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
The inner-shell photoionization of highly charged ions is studied, together with their subsequent radiative decay, within the framework of the density matrix theory and the multiconfiguration Dirac-Fock (MCDF) approach. For the subsequent radiative decay of the ions, we investigate in particular how the linear polarization of characteristic radiation is affected if the incident light is itself polarized. Detailed calculations are performed for the 2p53s→2p6 radiative transitions following the production of a 2p vacancy in the sodiumlike Fe15+, W63+, and U81+ ions. From these calculations, it is shown that the (degree of) linear polarization of the characteristic radiation may be enhanced by a factor of 2 due to the polarization transfer from the incident light.